Anaerobic digestion of organic wastes in Kenya: Biomethane yields and circular bioeconomy opportunities - Mulat, Daniel; Ngwa, M.; Fantahun, T.; Mwangi, Stanley (International Livestock Research Institute, 2025)
Kenya generates significant volumes of organic waste from urban markets, households, livestock farms, and slaughterhouses, which pose serious environmental, health, and climate risks due to poor waste management. At the same time, these wastes represent untapped potential for clean energy production via anaerobic digestion. This study assessed the biomethane potential (BMP) of representative organic waste streams in Kenya to inform biogas investment and circular economy transitions.